Different subsidies' impact on equilibrium decision-making of closed-loop supply chain - Liurui Deng; Wei Li; Zilan Liu (Journal of Industrial Engineering and Management (JIEM), 2014)
Purpose: An electronic product recycling not only needs the waste treatment company, but also involves recycler and remanufacturer. It is significance for increasing subsidy modes and promoting waste recycling to research the effect of government subsidies for recycler and remanufacturer on the equilibrium of closed-loop supply chain. Design/methodology/approach: In view of service competition, we build a Stackelberg model which contains an original manufacturer, a recycler and remanufacturer and further obtain the equilibrium decision of closed-loop supply chain. Based on this strategy model, we analyze how two different subsidies to utilization rate of raw materials, the service level and the demand of product affect on the terminal decision. Findings: We compared the two different subsidy ways in closed-loop supply chain. Subsidy to utilization rate of raw materials has no effect on the whole market demand for electronic product; and subsidy on utilization rate of raw materials has no effect on the whole market demand for electronic product. Research implications: Under the conditions in which government can observe the information of raw material utility and remanufacturing service level, if government decides to expand the market size, it could subsidize remanufacturer for different service level; Under the conditions in which government can observe the information of raw material utility and remanufacturing service level, if government want to improve utilization rate of raw materials, stimulate sustainable development of industries of electronic product, it can subsidizes recycler based on different utilization rate of raw materials. Originality/value: We analyzed the closed-loop supply chain equilibrium, compared the effects on it under different subsidy mechanism and offered some advises in order to provide scientific support to promote electronic products recycling.
Keywords: 650; subsidy; service; closed-loop supply chain; utilization rate of raw materials; decision-making